THE CONCEPT OF INTELLIGENCE AND REVELATION IN THE MU’TAZILAH SCHOOL OF THOUGHT - Hanan, Abdul (Journal of Islamicate Studies, 2019)
The school of Mu'tazilah thought in the development of Islamic thought is a very interesting and significant study. It is interesting, because the Mu'tazilah school is the oldest and the largest school of Islamic theology that has played an important role in Islamic world thought. Another interesting thing is that Mu'tazilah is a representation of the consciousness of the Islamic world in its progress and modernity. Intellect is the power of thought to understand something, in which there is a possibility that the understanding gained by reason can be wrong can also be true. Revelation is the word of God conveyed to his prophet both for himself and to be conveyed to the people. Knowledge is the relationship between subject and object, while science is knowledge that has been scientifically tested and the truth is clear. Reason and revelation are used to gain knowledge for mankind. Between reason and revelation there is a space where both can meet and even interact with each other and there is a space where they must separate. At the time the revelation recommended the development of science and the preservation of culture by providing space for freedom for reason to think dynamically, creatively and openly, there was a meeting space between reason and revelation. So that the relationship between reason and revelation is not contradictory but is very related between one another, even both of them perfect each other